Pathogenesis of human mitochondrial diseases is modulated by reduced activity of the ubiquitin/proteasome system - Segref, Alexandra; Kevei, Éva; Pokrzywa, Wojciech; Schmeisser, Kathrin; Mansfeld, Johannes; Livnat-Levanon, Nurit; Ensenauer, Regina; Glickman, Michael H; Ristow, Michael; Hoppe, Thorsten (Cell metabolism, 2014)
Mitochondria maintain cellular homeostasis by coordinating ATP synthesis with metabolic activity, redox signaling, and apoptosis. Excessive levels of mitochondria-derived reactive oxygen species (ROS) promote mitochondrial dysfunction, triggering numerous metabolic disorders. However, the molecular basis for the harmful effects of excessive ROS formation is largely unknown. Here, we identify a link between mitochondrial stress and ubiquitin-dependent proteolysis, which supports cellular surveillance both in Caenorhabditis elegans and humans. Worms defective in respiration with elevated ROS levels are limited in turnover of a GFP-based substrate protein, demonstrating that mitochondrial stress affects the ubiquitin/proteasome system (UPS). Intriguingly, we observed similar proteolytic defects for disease-causing IVD and COX1 mutations associated with mitochondrial failure in humans. Together, these results identify a conserved link between mitochondrial metabolism and ubiquitin-dependent proteostasis. Reduced UPS activity during pathological conditions might potentiate disease progression and thus provides a valuable target for therapeutic intervention.